Integrating Activity Based Costing (ABC) with Enterprise Resource Planning (ERP) for Effective Management: A Literature Review - Kitsantas, Thomas; Vazakidis, Athanasios; Stefanou, Constantinos (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
In the age of a global competition environment, the accurate costing measurement is important for planning and decision-making. To achieve this goal, contemporary costing methods are tested and applied such as the Activity Based Costing (ABC) in conjunction with the use of modern Information Technology (IT). The review study attempts a comparative analysis of both ABC and Traditional Costing Accounting (TCA), examining the main themes emerging from academic research and practitioners concerning the challenges, benefits, and barriers of ABC, analyzing the impact of the integration between ERP and ABC systems and its effect on management performance. A review of the literature generated an initial pool of 322 studies. Upon extensive review, 38 studies were found to be relevant to this topic. It appears from the review and analysis of the academic literature and professional sources that a successful integration among ERP and ABC minimizes the operation costs, enhances competitiveness, improves the management of the enterprise, due to its abilities to provide more accurate costing information for a strategic decision. However, practical implications in adopting ABC under ERP could be very challenging, requires a huge amount of internal resources, commitment among employees, and top management. In closing, additional research studies employing both qualitative and quantitative methods as well as case studies are needed in order to provide insights into the impact of ERP and detailed implications of how the ABC accounting system is adapting to the ERP environment and its effect on firm performance.